Prevention Effect of Protopanaxadiol-Type Saponins Saponins and Protopanaxatriol-Type Saponins on Myelosuppression Mice Induced by Cyclophosphamide - Zhang, He; Zhang, Lancao; Yang, Chunhui; Zhang, Yuyao; Li, Jing; Zhang, Xu; Chen, Jinjin; Huang, Baotai; Zhao, Daqing; Li, Xiangyan; Zhang, Wei; Qi, Bin (Frontiers in Pharmacology, 2022)
Ginsenosides from ginseng are used as a therapeutic agent for various diseases, which enhanced the immunomodulatory effect in cyclophosphamide (CP)-treated tumor disease. According to the structural characteristics of steroidal saponins, which were mainly divided into protopanaxadiol-type saponin (PDS) and protopanaxatriol-type saponin (PTS). At present, few researchers have studied which kind of saponin plays a more important role, thus, we compared the prevention effect of PDS and PTS on myelosuppression mice. The components and contents of saponin and monosaccharide were analyzed by using UPLC-CAD and RP-HPLC, respectively. Thirty-two mice were randomly divided into four groups: control, model , PDS and PTS. The mice were orally administered with PDS or PTS for 28 days, and then injected with CP saline solution on 25, 26, 27 and 28 days. After the end of modeling, the whole blood of mice was collected to detect routine blood tests, inflammatory cytokines, and hematopoiesis-related cytokines. Cell cycle and apoptosis of bone marrow in the right femur were detected. The spleen and thymus were weighted to calculate the organ index and histological examination, and splenocytes were used to detect the percentage of CD4+ and CD25+ T cells. In the saponins analysis, PDS mainly included the Rb1, Rc, Rb2 and Rd of protopanaxadiol-type ginsenosides (accounted for 91.64 %), and PTS mainly included the Re, Rg1 and Rf of protopanaxatriol-type ginsenosides (accounted for 75.46 %). The animal results showed that both PDS and PTS improved the most indicators of myelosuppression mice induced by CP, including increased the weight, blood cell numbers, hematopoiesis-related cytokines and inflammatory cytokines; promoted the cell cycle of bone marrow and inhibited the apoptosis of bone marrow; elevated the spleen and thymus indexes and CD4+ count of splenocytes. The prevention effect of PDS was better than PTS in some indicators, such as red blood cells, hemoglobin, interleukin (IL)-1β, IL-4, IL-10, tumor necrosis factor-α, CD4+ and thymus index. These results suggest both PDS and PTS can enhance the immune function of myelosuppression mice by CP. PDS shows high bioavailability and bioactivity compared with PTS, because of the effect of PDS itself or compound K of its metabolites.